Evaluasi Kebijakan Disiplin Pegawai Negeri Sipil Dalam Meningkatkan Efektivitas Penyelenggaraan Pemerintahan Di Kota Ternate - Sadik, Mira; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (Sam Ratulangi University, 2015)
Abstract: Research in the area of Secretariat and staffing agency areas of ternate city in theframework of the preparation of Thesis in proposing to meet one of the conditions to get acollege degree holdersThe discipline policy of civil servants in government agencies at boththe environment as well as the area has long been applied through the implementation of theGovernment Regulation number 53 in 2010 about disciplinary rules, civil servants, but so farit still found the behavior of CIVIL SERVANTS who Deviate even happening abusiveauthority thus implies a decrease in the performance of CIVIL SERVANTS so affected on thelow effectiveness of government organizations themselvesThis research aims to: know theimpact of policy discipline of civil servants against effectiveness of running government in thecity of ternate . The results of this study are expected to provide benefits, either theoreticallyor practically, theoretical research results is expected to enrich the development of socialscience, particularly the study of public administration. in practical research results is alsoexpected to contribute to the thinking of policy makers, in particular for the Government ofthe city of ternate and other related parties to solve practical problems in particularproblems related , either directly or indirectly with the construction of the civil servants inorder to increase Work discipline expected positive impact for increasing the effectiveness ofthe Organization of the Government Fore, ternate city.The conclusion of the Organization of the Government, particularly in the area of Secretariatand staffing agency Area ternate city has done enough effectiveness although not optimal, theresults of the analysis of the data showed that between the discipline of employees workingwith the effectiveness of the Government on Secretariat staffing agencies of regional and cityareas of ternate relationship connectedness and influence its nature kontributif as well as thevery real or significantAdvice is necessary to provide some suggestion that the first to raiseawareness of discipline , then required increase supervision , good functional monitoring tosurveillance and , both in government can increase the effectiveness of the optimization workdiscipline employees other than through , the government also need to activate the city ofternate functional training to improve the quality of human resources employeesKeywords: civil servants disciplinary policy & effectiveness of the Organization of theGovernment